2008
DOI: 10.1038/ijo.2008.111
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body vibration slows the acquisition of fat in mature female rats

Abstract: Objective: To evaluate the effects of whole-body vibration on fat, bone, leptin and muscle mass. Methods/Design: Thirty 7-month-old female 344 Fischer rats were randomized by weight into three groups (baseline, vibration or control; n ¼ 8-10 per group). Rats in the vibration group were placed inside individual compartments attached to a Pneu-Vibe vibration platform (Pneumex, Sandpoint, ID, USA) and vibrated at 30-50 Hz (6 mm peak to peak) for 30 min per day, 5 days per week, for 12 weeks. The vibration interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 37 publications
1
61
0
4
Order By: Relevance
“…Although the mechanism responsible for the increased body weight was not studied, it is assumed that the observed body weight gain may be the result of higher muscle mass and bone mass and/or the result of higher blood fl ow leading to the alteration on the peripheral vascular and tissue perfusion. Maddalozzo et al 2008 reported that mature female vibrated rats weighed 10 less, with less body fat and serum leptin concentrations 8 . Interestingly, in the AF group Gr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism responsible for the increased body weight was not studied, it is assumed that the observed body weight gain may be the result of higher muscle mass and bone mass and/or the result of higher blood fl ow leading to the alteration on the peripheral vascular and tissue perfusion. Maddalozzo et al 2008 reported that mature female vibrated rats weighed 10 less, with less body fat and serum leptin concentrations 8 . Interestingly, in the AF group Gr.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, whole body vibration has been proposed as a potential alternative, or adjuvant, to exercise 8 25 , reducing the risk of bone fracture more than walking 26 , increasing the serum levels of testosterone and growth hormone 27 , and representing no stressful stimulus for the neuroendocrine and neuromuscular systems 27,28 . Further, it would be well-advised to determine the infl uence of WBV on CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting the use of WBV as exercise in DD, WBV slowed the acquisition of fat in female rats [242] and improved pain and fatigue in women with fibromyalgia [243] .…”
Section: Dd Treatment Recommendationsmentioning
confidence: 99%
“…Maddalozzo et al 1 recently reported that 12 weeks of wholebody vibration (WBV) reduced body fat accumulation and serum leptin levels in rats. Taken at face value, these results are potentially important to the treatment of obesity.…”
mentioning
confidence: 99%